Benefits of wonder process craft on engine valve train performance. (April 2019) - Abdullah, M Usman; Shah, Samiur Rahman; Bhutta, M Usman; Mufti, Riaz Ahmad; Khurram, Muhammad; Najeeb, M Huzaifa; Arshad, Waseem; Ogawa, Kiyo
The performance and durability of tribological components in roller follower valve train is governed mainly by the roller rotational behaviour. Pure rolling of roller on the camshaft surface is essential to achieve the optimum valve train efficiency. The increase in roller slip can lead to high valve train power loss due to increase in sliding friction and can increase the wear rate of mating surfaces of camshaft and roller. In this research work, a modern gasoline engine having end-pivoted roller finger follower valve train configuration has been instrumented to investigate the effects of Wonder Process Craft surface treatment on roller slip. Comprehensive test programme has been undertaken at transient camshaft speeds by employing the New European Drive Cycle under different oil temperatures and pressures. Remarkable reduction in roller slip was recorded for Wonder Process Craft surface treated roller as compared to the original unmodified roller indicating its strong potential of employment in engine valve train. The test rig, surface treatment of roller, instrumentation, experimentation, results and discussion have been presented in detail in this paper.